Pelatihan Pemetaan Bisnis dengan Tools Online debagai Upaya Peningkatan Penjualan Produk Fashion Muslim - Novi Yanti Sandra Dewi; Muhammad Zaki Abdillah; Muhammad Haikal; Rema Supiana; Nurlaili, Nurlaili (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
In the digital era, effective business mapping is crucial for driving growth and increasing sales, particularly in the competitive fashion industry. Gumi store, as a Muslim fashion business, has experienced stagnation in sales and has yet to implement comprehensive business mapping to formulate the right strategy. This community service initiative aims to address this issue through intensive training focused on utilizing the Business Model Canvas (BMC) as an online strategic tool. The method employed in this activity involves training on the use of BMC for the owner and three employees of gumi store. This training includes interactive sessions that provide a fundamental understanding of the key elements in the BMC and how to integrate them into business strategy. The training evaluation was conducted through a practical project, where participants were required to create a customized BMC for gumi store. The results of this activity show that participants followed the training with high enthusiasm and were able to apply the knowledge gained in their business mapping. By using BMC, gumi store is expected to design a more effective and focused business strategy, which will have a direct impact on increasing sales and competitiveness in the Muslim fashion market. This community service program not only enhances gumi store’s internal capacity but also demonstrates the importance of utilizing digital tools in modern business development.